2023
DOI: 10.1108/jed-10-2022-0189
|View full text |Cite
|
Sign up to set email alerts
|

Individualism and climate change policies: international evidence

Abstract: PurposeThis paper aims to examine the extent to which the cultural dimension of individualism/collectivism matters for international differences in climate change policy performance. This study postulates that individualistic societies, relative to their collectivistic counterparts, are more likely to address global climate change.Design/methodology/approachThe main hypothesis is tested using data for a world sample of up to 92 countries. To achieve causal inference, this study isolates exogenous sources of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…1B). This effect remained significant (β = -0.10, SE = 0.03, t(58.56) = -3.62, p < .001, d = -0.95) when statistically adjusting for national GDP and participants' age, gender, income, political ideology, and education level, conceptually replicating prior work [30,33,34,35,43], and supporting the conclusion that individualism might be a problematic factor in the fight against climate change.…”
Section: Climate Beliefs and Behaviors Differ Across The Individualis...supporting
confidence: 75%
See 1 more Smart Citation
“…1B). This effect remained significant (β = -0.10, SE = 0.03, t(58.56) = -3.62, p < .001, d = -0.95) when statistically adjusting for national GDP and participants' age, gender, income, political ideology, and education level, conceptually replicating prior work [30,33,34,35,43], and supporting the conclusion that individualism might be a problematic factor in the fight against climate change.…”
Section: Climate Beliefs and Behaviors Differ Across The Individualis...supporting
confidence: 75%
“…Conversely, other research found individualism was more predictive of climate action [41,42,43]. For example, individualistic countries implemented more climate change policies in a study of 92 countries [43].…”
mentioning
confidence: 92%